The relationship between rehabilitation motivation and upper limb motor function in stroke patients - Li, Wenxi; Zhu, Guangyue; Lu, Yang; Wu, Jinglei; Fu, Zhuoxin; Tang, Junyi; Zhang, Guohui; Xu, Dongsheng (Frontiers in Neurology, 2024)
Objective Insufficient motivation among post-stroke survivors may be an important factor affecting their motor function recovery. This study seeks to investigate the relationship between motivation and functional recovery in stroke patients undergoing rehabilitation training. Materials and methods 103 stroke patients with upper limb impairments were studied during their hospital stays. Assessments were done before and after rehabilitation training to measure motivation, emotional state, motor function, and independence in daily activities. Data analysis was conducted to examine the distribution of these factors among the participants. Pearson and Spearman correlation analyses were used to study the relationships between motivation, emotional state, and motor function. Patients were divided into high and low motivation groups based on the Rehabilitation Motivation Scale (RMS), and chi-square and rank-sum tests were used to compare functional differences before and after treatment among patients with varying levels of motivation. Results 66 participants were found to have low motivation in the initial assessment of the RMS (64.08%). Consistency in motivation levels was observed among patients with high motivation (r = 0.648, P<0.001). Apathy was identified as the main factor affecting motivation in patients with low motivation (p = 0.027), while depression and anxiety were not significantly correlated. Motivation was strongly linked to improvements in upper limb motor function, daily living activities, and self-exercise duration (p < 0.001) for stroke patients undergoing rehabilitation. Post-training, there was a notable increase in motivation, motor function, and independence in daily activities (p < 0.001). Increased rehabilitation motivation was linked to better upper limb motor function and daily independence in patients, particularly those with low motivation. This correlation was significant for both the FMA-UE and FIM scores. Discussion Old patients with poor upper limb motor function often have low motivation, which hinders their recovery. Using strategies to boost motivation in stroke patients with impaired upper limb function could greatly improve their rehabilitation and motor skills. It is crucial to prioritize these intervention strategies. Conclusion Enhancing rehabilitation motivation in stroke patients with low motivation and upper limb motor impairments can foster the restoration of their functional capabilities.